Role of the lateral parabrachial nucleus in the control of sodium appetite - Menani, José Vanderlei [UNESP]; De Luca, Laurival A.; Johnson, Alan Kim (Amer Physiological Soc, 2014)
In states of sodium deficiency many animals seek and consume salty solutions to restore body fluid homeostasis. These behaviors reflect the presence of sodium appetite that is a manifestation of a pattern of central nervous system (CNS) activity with facilitatory and inhibitory components that are affected by several neurohumoral factors. The primary focus of this review is on one structure in this central system, the lateral parabrachial nucleus (LPBN). However, before turning to a more detailed discussion of the LPBN, a brief overview of body fluid balance-related body-to-brain signaling and the identification of the primary CNS structures and humoral factors involved in the control of sodium appetite is necessary. Angiotensin II, mineralo-corticoids, and extracellular osmotic changes act on forebrain areas to facilitate sodium appetite and thirst. In the hindbrain, the LPBN functions as a key integrative node with an ascending output that exerts inhibitory influences on forebrain regions. A nonspecific or general deactivation of LPBN-associated inhibition by GABA or opioid agonists produces NaCl intake in euhydrated rats without any other treatment. Selective LPBN manipulation of other neurotransmitter systems [e. g., serotonin, cholecystokinin (CCK), corticotrophin-releasing factor (CRF), glutamate, ATP, or norepinephrine] greatly enhances NaCl intake when accompanied by additional treatments that induce either thirst or sodium appetite. The LPBN interacts with key forebrain areas that include the subfornical organ and central amygdala to determine sodium intake. To summarize, a model of LPBN inhibitory actions on forebrain facilitatory components for the control of sodium appetite is presented in this review.
Keywords: sodium intake; angiotensin; electrolyte balance; thirst